PENERAPAN MEDIASI PENAL BERBASIS MASYARAKAT MELALUI RUMAH RESTORATIVE JUSTICE DI KEJAKSAAN NEGERI BONDOWOSO - Andhita Alvionita; Yudha Bagus Tunggala Putra (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Restorative Justice is an approach in criminal case resolution that prioritizes reconciliation and restoration. This approach involves bringing together the victim, the offender, and relevant members of the community to engage in dialogue with an emphasis on consensus and mutual agreement. The foundation for resolving cases using Restorative Justice is regulated by the Indonesian Prosecutor’s Regulation No. 15 of 2020 on the Termination of Prosecution Based on Restorative Justice. The focus of this research in this thesis is: (1) How is the implementation of Community-Based Penal Mediation through the Restorative Justice House established by the Bondowoso District Attorney's Office? (2) What is the effectiveness of the implementation of Community-Based Penal Mediation through the Restorative Justice House at the Bondowoso District Attorney's Office? This research aims to examine the implementation of Community-Based Penal Mediation through the Restorative Justice House established by the Bondowoso District Attorney's Office and to assess the effectiveness of the application of Community-Based Penal Mediation through the Restorative Justice House at the Bondowoso District Attorney's Office. Restorative Justice merupakan pendekatan dalam penyelesaian perkara pidana dengan mengedepankan perdamaian dan pemulihan Kembali. Dalam penyelesaian keadilan restoratif ini dengan mempertemukan korban dan pelaku serta masyarakat terkait untuk melakukan dialog dengan mengedepankan musayawarah mufakat. Dasar penyelesaian perkara dengan mengggunakan Restorative Justice yakni Peraturan Kejaksaan Republik Indonesia Nomor 15 Tahun 2020 Tentang Penghentian Penuntutan Berdasarkan Keadilan Retoratif. Pada fokus penelitian ini skripsi ini yaitu (1) Bagaimana Pelaksanaan Mediasi Penal Berbasis Masyarakat Melalui Rumah Restorative Justice Yang Di Bentuk Oleh Kejaksaan Negeri Bondowoso? (2) Bagaimana Efektifitas Penerapan Mediasi Penal Berbasis Masyarakat Melalui Rumah Restorative Justice Kejaksaan Negeri Bondowoso? Dan dalam penelitian ini bertujuan mengetahui Bagaimana Pelaksanaan Mediasi Penal Berbasis Masyarakat Melalui Rumah Restorative Justice Yang Di Bentuk Oleh Kejaksaan Negeri Bondowoso dan Untuk mengetahui Bagaimana Efektifitas Penerapan Mediasi Penal Berbasis Masyarakat Melalui Rumah RestorativeJustice Kejaksaan Negeri Bondowoso.